Pengembangan Lembar Kerja Peserta Didik Materi Pemanasan Global Berbasis Problem Based Learning Terintegrasi Nilai untuk Meningkatkan Hasil Belajar Peserta Didik - Nur Arafah; Sulastri Sulastri*; Safrida Safrida (Universitas Syiah Kuala, 2023)
Preliminary study results show that the science teacher at SMP Negeri 1 Banda Aceh still predominantly use teaching materials that have not been integrated with values yet, so that learners are less mastery in science concepts that related with values. Science learning outcomes students are still low based on national examination. Therefore, research centered on student worksheet development. This study aims to develop and determine the quality of problem based learning (PBL) worksheet that integrated with religious and practical values to improve students’ learning outcome on global warming chapter. This study uses research and development (RD) methods with the Borg and Gall model. The research subject were validators that consist science learning expert, natural science teachers, students of SMP grade VII. 31 students of SMP Negeri 1 Banda Aceh that selected as sample by purposive sampling technique. The instruments used were validation sheets, response questionnaires, pretest and posttest. The data analysis techniques are the percentage equation and independent-sample t-test. The results showed that the quality of the PBL worksheet could improve students’ learning outcome, as evidenced by the results of the quality assessment from expert validators obtained an average of 88.1% with a very decent category. There is significant difference in the average between posttest and pretest learning outcome after implementing the PBL student worksheets that integrated with religious and practical values. Therefore, the results obtained that the PBL worksheets is worthy to use as teaching materials in improving student learning outcomes